A Multi-Scale Approach to Predict the Impact Resistance of Braided Composites using Progress Failure. Issue 1 (January 2017) - Lei, Xu; Hayat, Khazar; Ha, Sung Kyu
A novel multi-scale approach based on micromechanics of failure together with the progressive damage models of the fibre and matrix constituents is presented to predict the impact resistance of braided composites. The meso- and micro-scale unit-cells of the braided composites with both thermosetting and thermos-plastic resin systems, were employed, and the effective properties of the braided tows, in the meso unit cell, were updated using the micro unit cell for which the degradation of constituent material properties were incorporated.